Comparison of different diagnostic methods in infants for differentiating idiopathic neonatal hepatitis from biliary atresia - Hasan, Md Mahmudul; Rahman, Mosfika; Hassan, Md Namely; Islam, ANM Shamsul; Rahman, Mohammad Ahmadur; Alam, Md Shafiul; Biswas, Rana Kumar; Karim, ASM Bazlul; Rukunuzzaman, Md (Journal of Preventive and Social Medicine, 2024)
Background: Biliary atresia (BA) and idiopathic neonatal hepatitis (INH) are two most common etiologies of neonatal cholestatic jaundice. It is important to distinguish INH from BA biliary atresia in an infant. The study was conducted to compare of different diagnostic methods in infants in differentiating INH and BA. Methods: This cross-sectional study was conducted at the Department of Pediatric Gastroenterology & Nutrition, BSMMU during the period from July 2018 to June 2019 among infants with neonatal cholestasis. Total 50 cholestatitic cases were selected through purposive sampling. A thorough history and physical examination were done and liver enzymes were studied. Abdominal ultrasonography, hepatobiliary scintigraphy and liver biopsy were done in all cases. Clinical parameter and investigational sensitivity, specificity, and diagnostic precision were calculated. To diagnose BA and INH, liver biopsy was considered the gold standard. Results: Among the participants, 72% were diagnosed as BA and 28% were INH. More than half of patients were male. There exists significant difference of birth weight and term baby between BA and INH. Presence of persistent pale coloured stool was more commonly seen in patients with BA. Diagnostic accuracy of persistent pale coloured stool, birth weight (normal) and term baby were 94%, 92% & 88% respectively. Sensitivity and specificity of Gammaglutamyl transpeptidase (GGT) in differentiating cases with BA and INH with cut point of ≥430.0 U/L were 86.1% and 85.7%, respectively. Hepatobiliary scintigraphy is found to have a better sensitivity than ultrasonography. GGT had diagnostic accuracy 86%, hepatobiliary scintigraphy had diagnostic accuracy 88% & USG had diagnostic accuracy 80% for BA and INH. Conclusion: Among the studied clinical parameters persistent pale coloured stool was most accurate to suggest the presence of BA. Serum level of GGT at cut-off value ≥ 430 U/L may be used as a reliable laboratory parameter to differentiate INH and BA. Hepatobiliary scintigraphy found to have a good sensitivity for BA. Positive result of hepatobiliary scintigraphy may be used as BA in infants with cholestasis. JOPSOM 2023; 42(1):14-20